The Influence of the Fraud Heptagon on Fraud Levels in Indonesian State-Owned Enterprises: The Moderating Role of the Whistleblowing System - Widiar Onny Kurniawan; Prayogi, Gusti Dian (Universitas PGRI Adi Buana, 2025)
This study aims to explore the correlation between the theoretical construct of the Fraud Heptagon and the intensity of fraudulent practices in Indonesian State-Owned Enterprises (SOEs), as well as the moderating role of the whistleblowing system in this relationship. The Fraud Heptagon is a concept that expands upon previous theories, such as the Fraud Triangle and Fraud Diamond, by incorporating additional elements that influence fraud occurrence, namely financial pressure, opportunity, rationalization, capability, arrogance, and greed. The whistleblowing system is identified as a control mechanism that can mitigate fraud risks within organizations by enhancing transparency and accountability. This research adopts a quantitative approach, systematically analyzing data to identify patterns in the relationships between variables. The analysis method employed is Moderated Regression Analysis (MRA), a statistical technique that allows for testing interaction effects between the independent variable and the moderating variable in influencing the dependent variable. Data processing is conducted using SPSS version 26, which provides advanced analytical capabilities for estimating regression coefficients and testing the significance of relationships. Data collection is carried out through a survey targeting SOE auditors using purposive sampling. The findings indicate that the Fraud Heptagon has a positive and significant influence on the level of fraud (β = 0.42; Sig. 0.001), suggesting that the more complex the factors within the Fraud Heptagon, the higher the potential for fraudulent practices. The whistleblowing system is found to have a negative and significant impact on fraud (β = -0.35; Sig. 0.002), demonstrating that an effective reporting system can suppress fraudulent activities within an organization. Moreover, the moderating effect of the whistleblowing system on the relationship between the Fraud Heptagon and fraud is also significant and negative (β = -0.28; Sig. 0.004), indicating that the more effective the whistleblowing system, the weaker the relationship between the Fraud Heptagon and fraud levels